Changes in Clinical Presentation and Epidemiology of Respiratory Pathogens Associated With Acute Respiratory Illness in Military Trainees After Reintroduction of Adenovirus Vaccine. (1st September 2015) - Yun, Heather C.; Young, Adam N.; Caballero, Manuel Y.; Lott, Lisa; Cropper, Thomas L.; Murray, Clinton K.
Abstract : Adenovirus vaccine reintroduction in military trainees has resulted in dramatic decreases in adenovirus disease, with no observed serotype shift, and milder illness in trainees with upper respiratory infection. However, other pathogens, especially rhinovirus, are detected with increasing frequency. Abstract: Background.  Adenovirus (Ad) has long been the predominant cause of acute respiratory illness (ARI) in military trainees. In 2011, live oral Ad vaccines for serotypes 4 and 7 were reintroduced into US basic military training populations. This study evaluated the impact on clinical presentations and other respiratory pathogens. Methods.  The Center for Advanced Molecular Detection at Joint Base San Antonio-Lackland prospectively collects demographic, clinical, and polymerase chain reaction data from respiratory specimens (throat swab and nasal wash) among Air Force trainees presenting for care of ARI. Results.  From June 2008 to August 2013, 2660 trainees enrolled and were tested for selected respiratory pathogens. Post-vaccine introduction (VI), reported systemic symptoms were less frequent, including fever (38% vs 94%) and myalgia (37% vs 67%; P < .01). Median temperature and heart rate decreased (98.4 vs 101.3°F, 81 vs 96 beats per minute; P < .01). Ad detection decreased for all Ad (3% vs 68%), Ad4 (1% vs 70%), 7 (0% vs 8%), 14 (0% vs 5%), and 3 (0.1% vs 2%); P < .01). Rhinovirus and cases with no pathogen identified increased in frequency (35% vs 18%, 51% vs 14%; P < .01). Conclusions.  Acute respiratory illness in military trainees post-VI is associated with decreased severity of systemic symptoms and reduced fever and heart rate. Marked reductions in frequency of Ad serotypes are seen, including those in the vaccine, with no serotype shift. However, detection of several other respiratory pathogens, most notably rhinovirus, is observed in increasing proportions, and a majority are now undiagnosed clinical syndromes.